Temporal Materialities: Ekphrasis and Suspension in Mike Wilson’s "Ciencias ocultas" (2019) - de los Ríos, Valeria (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
This article addresses Mike Wilson’s Ciencias ocultas from the notion of description as opposed to narration. In Wilson’s novel, the things described form part of a crime scene, which is never resolved, since the writing stops following the description of the things inside the crime scene. Among these, everyday objects appear, but also images that are described in the form of ekphrasis, a paradigmatic figure of the relationship between writing and image. Wilson’s work is read from the framework proposed by the new materialisms that give agency to matter, which has a vibrating power (Bennett). One of the main effects of the description in Ciencias ocultas is the slowdown and temporary suspension.